Organosilicon polymer brush ultra-smooth liquid surface material as well as preparation method and application thereof
By preparing and using the PDMS-G-POSS-G and PDMS-G-D-NH2 to achieve the preparation of the surface of the organic silicon polymer to brush the super-sliding fluid surface, it solves the lack of attachment and poor performance in the existing technologies. The problem realizes excellent adhesion, transparency and super slippery performance, and the process is safe and environmentally friendly.
Patent Information
- Application Number
- CN202411651553.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing method of building a silicone polymer brush super-slide surface has problems such as insufficient adhesion, poor light transmission and ultra-sliding performance, and low environmental protection and safety of the process, which limits its use on a wide range of substrates. application.
By preparing polydimethylsiloxane-modified glycidoxypropyl polyhedral cage polysilsesquioxane (PDMS-g-POSS-G) and aminopropylmethylcyclosiloxane (PDMS-g-D- NH2), using addition reactions to achieve the preparation of super-slippery liquid surface materials on a wide range of substrates.
It achieves excellent adhesion on a wide range of substrates, high transparency and excellent super slippery properties, and the process is safe and environmentally friendly, making it suitable for large-scale operations.
Smart Images

Figure CN119350627A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional materials, and in particular to an organosilicon polymer brush super-lubricant surface material and a preparation method and application thereof. Background Art
[0002] Super liquid-repellent surfaces, such as super-slippery surfaces and super-liquid-repellent surfaces, are special surface phenomena of solid materials, which refers to the excellent anti-liquid adhesion ability given to the surface by repelling the spread of liquid beads. Compared with super-liquid-repellent surfaces (including super-hydrophobic and super-oleophobic surfaces), super-slippery surfaces represented by silicone polymer brushes have greater advantages in light transmittance, wear resistance and liquid repellency spectrum. Therefore, the super-slippery surface of silicone polymer brushes has more ideal functions such as anti-microbial adhesion, anti-fingerprint, anti-corrosion, anti-icing, and fluid drag reduction.
[0003] At present, the methods for constructing super-slippery surfaces of silicone polymer brushes mainly include the following schemes:
[0004] (1) Hydrolysis and condensation self-assembly of silane monomers: The hydrolysis and condensation self-assembly of silane monomers is usually based on the condensation self-assembly of the hydrolysis products of alkyldimethoxysilane or alkyldichlorosilane to form silicone polymer brushes, such as the Chinese invention patent with application number: 202211226022.0 and the research papers with DOI: 10.1002 / adma.202100237 and 10.1002 / anie.201509385. In this method, the adhesion of the silicone polymer brush depends on the chemical interaction between the Si-OH of the hydrolysis product and the -OH of the substrate, resulting in the silicone polymer brush super-slip surface being only applicable to glass or a few metal substrates (such as aluminum and titanium), thus limiting its practical application in the fields of construction, electronics, biology, transportation, chemical industry, and medical treatment; in addition, the self-assembly of silane substances through hydrolysis and condensation has strict control over the reaction process and involves toluene or strong acid as a medium or catalyst, which is less environmentally friendly or safe and not conducive to large-scale operations.
[0005] (2) Curing and grafting of silicone polymers: Using polydimethylsiloxane (PDMS) terminated with active groups (amino, glycidyl ether, hydroxyl, etc.) and polymer (resin) monomers under the action of a curing agent (or initiator), co-curing to achieve grafted silicone polymer brushes, such as the Chinese invention patent with application number: 202211283011.6 and the research paper with DOI: 10.1002 / anie.201904210. However, in this scheme, since PDMS is a low surface energy substance, while the polymer monomer and curing agent / initiator are high surface energy substances, that is, the chemical matching between the components is low, resulting in thermodynamic instability of the slurry, poor coating leveling, and limited liquid-like activity of the polymer brush (activation is required), so the light transmittance and super-slip properties of the formed coating are worse than those of the first method (hydrolysis and condensation self-assembly).
[0006] In summary, there is an urgent need to provide a super-lubricant surface material that is safe, environmentally friendly, has excellent adhesion on a wide range of substrates, and has excellent light transmittance and super-lubricating properties. Summary of the invention
[0007] [Technical issues]
[0008] The technical problem to be solved by the present invention is to provide a safe, environmentally friendly, and silicone polymer brush super-slip surface material having excellent adhesion on a wide range of substrates, as well as excellent light transmittance and super-slip properties, as well as a preparation method and application thereof.
[0009] [Technical solution]
[0010] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0011] In a first aspect, the present invention provides a method for preparing a silicone polymer brush super-slip surface material, comprising the following steps:
[0012] S1. Preparation of PDMS-g-POSS-G (polydimethylsiloxane-modified glycidyloxypropyl polyhedral cage-type polysilsesquioxane):
[0013] PDMS-NH2 (amino-terminated polydimethylsiloxane) and POSS-G (glycidyloxypropyl polyhedral cage-type polysilsesquioxane) were dissolved in solvent A, heated for reaction, acetonitrile was added, and the upper liquid was collected to obtain a PDMS-g-POSS-G solution;
[0014] S2, PDMS-gD-NH2 (aminopropylmethylcyclosiloxane modified with polydimethylsiloxane) preparation:
[0015] Dissolve PDMS-G (glycidyl-terminated polydimethylsiloxane) and D-NH2 (aminopropylmethylcyclosiloxane) in solvent B, heat to react, obtain a reaction solution, collect the upper layer of the reaction solution, and obtain a PDMS-gD-NH2 solution;
[0016] S3. Preparation of super slippery surface materials:
[0017] The PDMS-g-POSS-G described in step S1, the PDMS-gD-NH2 described in step S2 and a catalyst are mixed and reacted to obtain a super-slippery surface material; the catalyst includes one or more of salicylic acid, imidazole, triethylamine, methyldiethanolamine, resorcinol, and benzyltriethylammonium chloride.
[0018] In one embodiment, the PDMS-NH2 in step S1 is double-terminated with aminopropyl groups. Optionally, the molecular weight of the PDMS-NH2 is 1000 to 15000.
[0019] In one embodiment, the concentration of PDMS-NH2 in step S1 is 2-40 mg / mL.
[0020] In one embodiment, the concentration of POSS-G in step S1 is 150-500 mg / mL.
[0021] In one embodiment, the cage type of POSS-G in step S1 includes T8, T 10 , T 12 One or more of .
[0022] In one embodiment, the ratio of the number of silicon atoms on the siloxane cage of the POSS-G in step S1 to the number of glycidyloxypropyl side chains is 40-100%.
[0023] In one embodiment, the solvent A and the solvent B are the same or different. The solvent A or the solvent B includes one or more of propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dimethyl carbonate, ethyl butyl carbonate, petroleum ether, and propylene carbonate.
[0024] In one embodiment, the heating reaction in step S1 is heating under reflux under stirring conditions.
[0025] In one embodiment, the heating reaction time of step S1 is not limited, as long as the reactants can react completely. Optionally but not limited, the heating reaction time of step S1 is 1-5 hours. Further, it can be 2 hours.
[0026] In one embodiment, the heating temperature in step S1 is 55-140°C.
[0027] In one embodiment, the PDMS-G described in step S2 is mono-terminated with glycidyloxypropyl.
[0028] In one embodiment, the molecular weight of the PDMS-G in step S2 is 800-12000.
[0029] In one embodiment, the concentration of PDMS-G in step S2 is 80-300 mg / mL.
[0030] In one embodiment, the D-NH2 described in step S2 is one or more of tetraaminopropyltetramethylcyclotetrasiloxane (D4-NH2), pentaaminopropylpentamethylcyclopentasiloxane (D5-NH2), hexaaminopropylhexamethylcyclohexasiloxane (D6-NH2), and octaaminopropyloctamethylcyclooctasiloxane (D8-NH2).
[0031] In one embodiment, the concentration of D-NH2 in step S2 is 120-350 mg / mL.
[0032] In one embodiment, the heating reaction in step S2 is heating under reflux under stirring conditions.
[0033] In one embodiment, the heating reaction time of step S2 is not limited, as long as the reactants can react completely. Optionally but not limited, the heating reaction time of step S2 is 1-5 hours. Further, it can be 2 hours.
[0034] In one embodiment, the heating temperature in step S2 is 55-140°C.
[0035] In one embodiment, the mixing volume ratio of PDMS-g-POSS-G and PDMS-gD-NH2 in step S3 is 1:0.5-4.
[0036] In one embodiment, the concentration of the catalyst in the catalytic system is 1 to 25 mg / mL.
[0037] In a second aspect, the present invention also provides a super-lubricant surface material prepared by the method described in the first aspect.
[0038] In a third aspect, the present invention further provides the use of the method described in the first aspect or the super-lubricant surface material described in the second aspect in the preparation of a super-lubricant coating.
[0039] In one embodiment, the application includes coating the super-lubricating liquid surface material on a substrate surface and drying to obtain a super-lubricating coating.
[0040] In one embodiment, the coating method includes any one or more of spray coating, brush coating, scraper coating, roller coating, spin coating, and dip coating.
[0041] In one embodiment, the substrate includes, but is not limited to, metal, glass, plastic, ceramic, fabric, paper, or leather.
[0042] In one embodiment, the thickness of the ultra-slip coating is less than 2 μm.
[0043] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here.
[0044] Compared with the prior art, the present invention has the following beneficial effects:
[0045] The present invention prepares a glycidyl ether monomer PDMS-g-POSS-G and an amine curing agent PDMS-gD-NH2 respectively, and uses the glycidyl ether monomer and the amine curing agent to cure through addition reaction, so that the glycidyl ether monomer and the amine curing agent have excellent adhesion on a wide range of substrates, thereby realizing the introduction of a super-slippery liquid PDMS polymer brush coating; the medium of the precursor slurry is a non- / low-toxic or safe substance, which can form a PDMS polymer brush coating by self-drying at room temperature on the surface of the substrate, which is conducive to large-scale operation; due to the good chemical matching of PDMS-g-POSS-G and PDMS-gD-NH2, the slurry is thermodynamically stable, has good coating leveling, and has strong liquid-like activity of the polymer brush, so that the formed coating has high transparency and excellent super-slip performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Contact angle and sliding angle of different liquids on the PDMS polymer brush coating surface.
[0047] Figure 2 The ethylene glycol sliding effect of the PDMS polymer brush coating on the glass surface before and after 50 tape tear tests. A represents before the tape test (0s), B represents before the tape test (0.5s), C represents after the tape test (0s), and D represents after the tape test (0.5s). DETAILED DESCRIPTION
[0048] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0049] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials and reagents used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0050] Example:
[0051] Embodiment 1:
[0052] In a round-bottom flask, PDMS-NH2 (15 mg / mL) with a molecular weight of 1000 and T8-type octa-side chain POSS-G (230 mg / mL) were dissolved in 100 mL of propylene glycol monomethyl ether, stirred and heated at 110°C for 2 h, cooled and added with 20 mL of acetonitrile, and the lower layer and sediment were removed to obtain a PDMS-g-POSS-G solution. In a round-bottom flask, single-terminated PDMS-G (125 mg / mL) with a molecular weight of 5000 and tetraaminopropyltetramethylcyclotetrasiloxane (D4-NH2, 146 mg / mL) were dissolved in 100 mL of propylene glycol monomethyl ether, stirred and heated at 110°C for 2 h, cooled and removed the lower layer to obtain a PDMS-g-D4-NH2 solution. 5 mL of PDMS-g-POSS-G solution was mixed with 10 mL of PDMS-g-D4-NH2 solution, and methyldiethanolamine (1 mg / mL) was added and stirred to form a precursor slurry. The precursor slurry was sprayed on the glass surface, and the thickness of the naturally leveled liquid film was about 30 μm. After drying at room temperature for 1.5 hours, a PDMS polymer brush coating was formed. Figure 1 As shown, the PDMS polymer brush coating has excellent super-lubricating properties for low surface tension liquids (such as hexadecane and n-hexane); Figure 2 As shown, the PDMS polymer brush coating on the glass surface is highly transparent, and the ethylene glycol sliding properties do not change significantly before and after 50 tape tear tests, indicating that the coating has excellent adhesion.
[0053] Embodiment 2:
[0054] In a round-bottom flask, PDMS-NH2 (18.5 mg / mL) with a molecular weight of 1200 and T8-type eight-side chain POSS-G (220 mg / mL) were dissolved in 100 mL of propylene glycol monomethyl ether, stirred and heated at 110°C for 2 h, cooled and added with 20 mL of acetonitrile, and the lower layer and sediment were removed to obtain a PDMS-g-POSS-G solution. In a round-bottom flask, single-end PDMS-G (125 mg / mL) with a molecular weight of 5000 and D4-NH2 (146 mg / mL) were dissolved in 100 mL of propylene glycol monomethyl ether, stirred and heated at 110°C for 2 h, cooled and removed from the lower layer to obtain a PDMS-g-D4-NH2 solution. 5 mL of PDMS-g-POSS-G solution was mixed with 10 mL of PDMS-g-D4-NH2 solution, and imidazole (1.5 mg / mL) was added and stirred to form a precursor slurry. The precursor slurry was sprayed on the stainless steel surface, and the thickness of the naturally leveled liquid film was about 30 μm. After drying at room temperature for 1.5 hours, a PDMS polymer brush coating was formed.
[0055] Embodiment 3:
[0056] In a round-bottom flask, PDMS-NH2 (14 mg / mL) with a molecular weight of 1000 and T12-type twelve-side chain POSS-G (300 mg / mL) were dissolved in 100 mL of butyl acetate, stirred and heated at 90°C for 2 h, cooled and added with 20 mL of acetonitrile, and the lower layer and sediment were removed to obtain a PDMS-g-POSS-G solution. In a round-bottom flask, single-terminated PDMS-G with a molecular weight of 5000 (125 mg / mL) and D4-NH2 (146 mg / mL) were dissolved in 100 mL of butyl acetate, stirred and heated at 90°C for 2 h, cooled and removed from the lower layer to obtain a PDMS-g-D4-NH2 solution. 5 mL of PDMS-g-POSS-G solution was mixed with 10 mL of PDMS-g-D4-NH2 solution, and methyldiethanolamine (1 mg / mL) was added and stirred to form a precursor slurry. The precursor slurry was sprayed on the ceramic surface, and the thickness of the naturally leveled liquid film was about 30 μm. After drying at room temperature for 1.5 hours, a PDMS polymer brush coating was formed.
[0057] Embodiment 4:
[0058] In a round-bottom flask, PDMS-NH2 (15 mg / mL) with a molecular weight of 1000 and T8-type octa-side chain POSS-G (220 mg / mL) were dissolved in 100 mL of propylene glycol monomethyl ether, stirred and heated at 110°C for 2 h, cooled and added with 20 mL of acetonitrile, and the lower layer and sediment were removed to obtain a PDMS-g-POSS-G solution. In a round-bottom flask, single-terminated PDMS-G (135 mg / mL) with a molecular weight of 3000 and hexaaminopropyl hexamethylcyclohexasiloxane (D6-NH2, 170 mg / mL) were dissolved in 100 mL of propylene glycol monomethyl ether, stirred and heated at 110°C for 2 h, cooled and removed the lower layer to obtain a PDMS-g-D6-NH2 solution. 5 mL of PDMS-g-POSS-G solution was mixed with 10 mL of PDMS-g-D6-NH2 solution, and resorcinol (1 mg / mL) was added and stirred to form a precursor slurry. The precursor slurry was sprayed on the surface of the PET film, and the thickness of the naturally leveled liquid film was about 30 μm. After drying at room temperature for 1.5 hours, a PDMS polymer brush coating was formed.
[0059] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. A method for preparing a silicone polymer brush super-slip surface material, characterized in that: The steps include: S1. Preparation of PDMS-g-POSS-G: Dissolve PDMS-NH2 and POSS-G in solvent A, heat to react, add acetonitrile, collect the upper liquid, and obtain PDMS-g-POSS-G solution; S2, PDMS-gD-NH2 preparation: Dissolve PDMS-G and D-NH2 in solvent B, heat to react, obtain a reaction solution, collect the upper layer of the reaction solution, and obtain a PDMS-gD-NH2 solution; S3. Preparation of super slippery surface materials: The PDMS-g-POSS-G in step S1, the PDMS-gD-NH2 in step S2 and a catalyst are mixed and reacted to obtain a super slippery surface material; the catalyst comprises one or more of salicylic acid, imidazole, triethylamine, methyldiethanolamine, resorcinol, and benzyltriethylammonium chloride; The solvent A and the solvent B are the same or different; the solvent A or the solvent B includes one or more of propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dimethyl carbonate, ethyl butyl carbonate, petroleum ether, and propylene carbonate.
2. The method according to claim 1, characterized in that The PDMS-NH2 described in step S1 is double-terminated with aminopropyl groups.
3. The method according to claim 1, characterized in that The cage type of POSS-G in step S1 includes T8, T 10 , T 12 One or more of .
4. The method according to claim 1, characterized in that: In step S1, the ratio of the number of silicon atoms on the siloxane cage of POSS-G to the number of glycidyloxypropyl side chains is 40-100%.
5. The method according to claim 1, characterized in that The PDMS-G described in step S2 is capped with a glycidyloxypropyl group.
6. The method according to claim 1, characterized in that The D-NH2 described in step S2 is one or more of tetraaminopropyltetramethylcyclotetrasiloxane, pentaaminopropylpentamethylcyclopentasiloxane, hexaaminopropylhexamethylcyclohexasiloxane, and octaaminopropyloctamethylcyclooctasiloxane.
7. A super-slippery liquid surface material prepared by the method according to any one of claims 1 to 6.
8. Use of the method according to any one of claims 1 to 6 or the super-lubricant surface material according to claim 7 in the preparation of a super-lubricant coating.
9. The use according to claim 8, characterized in that: The application comprises coating the super-slippery liquid surface material on the surface of a substrate and drying the super-slippery coating.
10. The use according to claim 9, characterized in that: The substrate includes metal, glass, plastic, ceramic, fabric, paper or leather.
Citation Information
Patent Citations
Preparation method of POSS modified polysiloxane rubber composite material
CN103849150A
Super-hydrophilic functional coating based on polyhedral oligomeric silsesquioxane and preparation method thereof
CN113372814A
Silsesquioxane modified low-temperature-resistant low-dielectric polysiloxane as well as preparation method and application thereof
CN117304490A